Promoting Inclusive Education Practices Through Parental Involvement: The Case Of Algerian Middle Schools - Khadidja, LATRECHE; Ahmed Chaouki, HOADJLI (جامعة الوادي - University of Eloued, 2021)
Abstract Inclusive education is one best way of ensuring the full access of students with and without disabilities in the educational process. Its main salient concern is to provide an equitable learning environment wherein all students are alike. Admittedly, there is ample evidence that the educational reform towards inclusive schools, if not allied with a profound understanding to the history of inclusion, would be slow. Reviewing the literature of inclusion highlights various critical factors that cement inclusive practices at schools. Parental involvement is one significant predictor of effective inclusion. This study, henceforth, aims at investigating middle school principals’ attitude towards parental involvement, and how far can this parents-schools synergy promote students’ academic achievement. In essence, it seeks at expanding the inclusive consciousness of parents, either they have children with special educational needs or they do not. To obtain the necessitated data, a cohort of 13 principals at the middle level was conveniently selected for the parental involvement interview. The obtained results from this qualitatively-oriented study reveal some positive and some other negative perceptions of school-parent relations on the part of principals. Recommendations for developing and improving parental involvement issues are henceforth provided.
Keywords: Algerian middle schools ; barriers to parental involvement ; inclusive education ; parental involvement ; principals’ attitude